Comparison of different capacity models for traffic circles - Çalışkanelli, Pelin; Özuysal, Mustafa; Tanyel, Serhan; Yayla, Nadir (Transport, 2009)
Traffic circles have been used in many countries all over the world. Traffic circles can be defined as intersections where traffic circulates around a center island where priority is given to the vehicles entering from branches and are designed considering weaving movements as the basic goal. There are two most common capacity analysis methods for traffic circles: the method of critical gap acceptance and the method of regression analysis. This study explains the methods of gap acceptance and regression analysis. Ashworth and Field method is investigated and the applicability of these capacity models in Turkey is discussed. The obtained results have shown that both methodologies give satisfactory results; however, the existing methods should be improved (modified) considering conditions.First published online: 27 Oct 2010